Comparative engineering economic analysis of a variable refrigerant flow and mini-split air conditioning system design - Layeni, A. T.; Olanrewaju, A. I.; Nwaokocha, C. N.; Waheed, M. A.; Giwa, S. O.; Kuye, S. I.; Adedeji, K. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
The design and comparative engineering economic analysis of two Air-conditioning (AC) systems, mini-split and variable refrigerant flow (VRF), for the new Engineering Complex Building, at the College of Engineering and Environmental Studies, Ibogun Campus of Olabisi Onabanjo University, under the same indoor and outdoor conditions for a one-year period was carried out using Carrier Hourly Analysis (CHA) program software for determining cooling load estimation, and the Net Present Worth Approach  for calculating the economic analysis of both systems’ design. The cooling load estimation was done using the American Society of Heating, Refrigeration and Air-Conditioning Engineers (ASHRAE) transfer function method rooted within the Carrier software. The total cooling load for the building was found to be 239,243 W. Equipment used in analysis was selected from the Toshiba selection catalogues (Mini Split system), while that for the VRF system was selected using Toshiba simulation software. The annual energy cost analysis of both systems revealed that the VRF system require more energy to run annually than the mini split system. However, the analysis was carried out without considering the part load potential energy savings of the VRF system. Results further indicated from the net present worth analysis carried out, the mini split system, in terms of Net Present Value of both systems, is more favoured. On the bases of the Engineering Economic Analysis carried out on the two systems, the overall Net Present Value for the VRF system was about  N78 million, while that of the mini-split system was about  N47 million. These results show that the VRF system had a higher cost implication than the mini-split system. Therefore, in terms of cost, the mini-split system was found to be a more viable option being an older and more established technology to the VRF system. In terms of design, the mini-split system, with equal number of indoor and outdoor units, is generally a system with more component units than the VRF system, with less outdoor units to indoor units, was expected to be more complicated and complex in design. However, control and operation flexibilities favour the mini-split system to the VRF system.